A Survey Of Solar Dish Cavity Receivers Geometries - Sarmad S. A. Talib; Ra'ad K. Mohammed Al Dulaimi (مجلة النهرين للعلوم الهندسية)
Recent scholarly efforts have extensively explored the efficacy of solar dish concentrators through both numerical simulations and empirical investigations. These studies predominantly scrutinize the interplay between solar receiver geometry and the dual objectives of minimizing heat loss while amplifying thermal efficiency. This comprehensive review synthesizes the spectrum of research dedicated to examining various cavity receiver geometries alongside their optimization techniques when integrated with parabolic dish collectors. We systematically assess configurations, including flat-sided, cylindrical, conical, and hemispherical designs. Our findings highlight that for an inlet temperature set at 200oC, the conical cavity receiver is distinguished by an exergy efficiency of 30%, a thermal efficiency approximating 70%, and an optical efficiency nearing 87%, maintaining a working fluid temperature range of 650°C to 750°C. The elevated operational temperatures, coupled with the inherent geometry of the cavity, accentuate the significance of mitigating heat losses attributed to convection, conduction, and radiation, as these factors critically impinge on system performance. Additional variables such as cavity inclination angle, diameter-to-depth ratio, tubing contour, and material selection are identified as instrumental in influencing cavity heat losses. Consequently, the pursuit of an optimized cavity receiver geometry emerges as a pivotal area of study. Drawing upon the issues analyzed, we propose strategic recommendations and conclude with insightful remarks poised to guide future research endeavors.